DBA Survivor Become a Rock Star DBA - LaRock, Thomas; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
DBA Survivor is a book to help new database administrators understand more about the world of database administration. More and more people are moving into the DBA profession, and many are looking for a getting-started guide. Blogs are written about how to be an exceptional DBA and what to do in your first 100 days. This book takes a different approach, injecting some humor into helping you understand how to hit the ground running, and most importantly how to survive as a DBA. And it$1 (Bs not just survival that matters. Author Thomas LaRock wants much more for you than mere survival. He wants you to have excellence, competence, visibility, confidence, and service. These are the traits and characteristics of DBAs who truly succeed and become respected in their profession. Don$1 (Bt settle for just muddling through your job each day. Strive to excel. Aim to make a difference, for your clients, and for your colleagues. Focuses on the soft skills that distinguish truly exceptional DBAs Takes a humorous approach to keep readers engaged Written by a SQL Server "Most Valuable Professional" and board member of PASSs
How Did I Get Here? -- Now What Do I Do? -- Some Basics -- A Development Server Is a Production Server to a Developer -- Production Support -- Basic Troubleshooting -- Where$1 (Bs the Buffet? -- Training, Get You Some of That -- Connect. Learn. Share. -- Summary.s
Keywords: Computer science; Computer Science; Programming Techniques